MUNDO DO TRABALHO E AVANÇOS TECNOLÓGICOS: DESAFIOS E PERSPECTIVAS DE PROJETOS PEDAGÓGICOS EM UNIVERSIDADES PÚBLICAS ESTADUAIS DO PARANÁ - Lozeckyi, Jeferson (2023)
The technological advances that occur rapidly worldwide have been causing increasing changes in all areas of society, with emphasis on the world of work, which is undergoing constant and significant changes. This has transformed the profiles of professionals required to operate in this increasingly technological environment. The new profiles require the mastery of skills that go beyond those that are merely technical and repetitive (hard skills), with the need to develop so-called soft skills. In this scenario, universities are called upon to provide solutions to the demands for new professionals, which the current world of work requires. In order to do this, they need to adapt their pedagogical projects, designing new professional profiles and working on the new professional skills required by this world of work. Given this scenario, the present study sought to answer the following problem: are the changes in the world of work and in the professional skills, resulting from technological advances, being considered by the pedagogical projects of undergraduate courses of public state universities of Paraná? This is an applied, exploratory research with a qualitative approach. As a methodological procedure, a Documentary Research was carried out. Using Bardin's Content Analysis, the pedagogical course projects (n=43) and the national curricular guidelines (n=11) of eight undergraduate courses, which are offered by three public universities in the State of Paraná, were analyzed. The institutional development plans of these universities were also analyzed. The results indicate that most of the pedagogical projects studied show more concern about complying with the course's DCNs, rather than being guided by them, not making use of the flexibility they allow. In most cases, these DCNs do not show great concern about changes in the world of work or the impacts of technological advances on professions. This ends up being reflected in pedagogical projects, as it was not identified that the impacts of these changes in the world of work or technological advances, on the professionals they train, are a reason for greater concern and discussion for the majority of the projects in the sample. As for the new professional skills required by the job market, with greater emphasis on soft skills, it was concluded that they can be inferred from professional profiles and forms of professional activity, but they are very little explained within the PPCs. The emphasis seems to be directed towards the formation of hard skills and the transmission of knowledge. Even when there is mention of soft skills, there is no objective description of how they can be formed in the student. The concern with keeping up with changes in the composition of professional skills was little noticed in the analyzed pedagogical projects.